Analysis of Premium Reserves in Whole Life and Term Life Insurance Using the New Jersey Prospective Method - Cabelita Husuna; Novianita Achmad; Agusyarif Rezka Nuha; Nisky Imansyah Yahya; Muhammad Yahya Ayyasy (Jurusan Matematika FMIPA Universitas Pattimura, 2025)
Human life is constantly exposed to risks such as illness, accidents, and death, which create financial uncertainties for individuals and families. Life insurance serves as an essential financial instrument to mitigate these risks by transferring potential liabilities to insurance companies. This study analyzes premium reserves for whole life and term life insurance using the New Jersey Prospective Method, applying a 6% interest rate and the 2023 Indonesian Mortality Table (TMPI) as the basis of calculation. Actuarial commutation functions are employed to compute annuity values, single net premiums, annual net premiums, and reserve allocations across different ages. The results indicate that reserve values increase with age, reflecting higher mortality risks, with whole life insurance showing a sharper escalation compared to term life insurance. The New Jersey Prospective Method demonstrates accuracy and consistency in reserve estimation, particularly by setting zero reserves in the first policy year, thereby supporting initial liquidity. These findings highlight the method’s effectiveness in maintaining financial stability and readiness of insurance companies to meet future claims and long-term obligations to policyholders.